The Application of Angulated Screw-Channels in Metal-Free, Implant-Supported Restorations: A Retrospective Survival Analysis - Edoardo Rella (MDPI AG, 2021)
Angulated screw channels (ASC) allow the clinician to reposition the access hole of screw-retained restorations, improving the design of the rehabilitation and the esthetic outcome. Few clinical studies are available on the efficacy of these restorations, especially at longer follow-ups and with a large number of subjects. The objective of this study was therefore to retrospectively evaluate patients rehabilitated with screw-retained restorations using ASC. The time of delivery and their adherence to the maintenance program was obtained, as well as the characteristics of the restoration and of the patient’s occlusion; a Kaplan–Meier survival curve was then built to investigate the success rate of these restorations and the effects of several variables were evaluated with a Cox model. A total of 105 subjects and 162 implants were enrolled in this study; after 42 months a success rate (92%) similar to what is reported for conventional screw-retained restorations was encountered. Monolithic zirconia restorations (n = 52) had a higher success rate (95%) when compared to partially veneered restorations (n = 53), which suffered a higher number of complications (90%). The other variables had no statistically significant effect. Implant supported prostheses adopting ASC provide a favorable outcome both in the posterior and anterior regions and can therefore be adopted to treat cases where the implant angulation is unfavorable for a conventional screw-retained prosthesis.